Pricing Strategy in Increasing Furniture Sales Volume at CV Sejahtera Abadi Jaya - Eva Ventiana; Nur Aini Anisa; Danang Apriliyanto (International Journal of Economics, Science, and Education, 2025)
This research explores the critical role of pricing strategy amid intense business competition, where economic development compels companies to optimize their business approaches. Pricing is a decisive factor influencing company sales volumes; thus, careful decision-making regarding price setting is essential to avoid negative impacts on sales. The study aims to describe the pricing process and analyze strategies used to increase sales volume. A qualitative method was employed, utilizing both primary and secondary data sources, with data collected through field interviews, observation, and documentation, particularly with company leadership. Findings at CV Sejahtera Abadi Jaya show that the company adopts a full cost plus mark-up pricing strategy, considering all production costs to set optimal prices. This approach has proven effective in increasing and maintaining sales volume over a six-month period (January–July), as evidenced by sales data, even though there was no increase in March, demonstrating the company’s ability to sustain consumer interest.